Comparison of a dynamic test to analyze the texture of cooked rice with a classic compression–extension test. Issue 11 (26th August 2014) - Park, Inmyoung; Kim, Seung‐Hyun; Chung, Ill‐Min; Kim, In‐Ho; Shoemaker, Charles F.; Seo, Young‐Su
<x xml:space="preserve">Abstract</x> This study was conducted to elucidate the inter‐relationships between the classical compression–extension test and the dynamic rheological test to analyze the texture of cooked rice with two different water ratios. The classical compression–extension test evaluated firmness and adhesiveness, after which the modified balance was calculated. Concurrently, a rheological test, tanδ and |G*| were used to analyze the data. The compression–extension test revealed that the firmness and modified balance increased, while adhesiveness was less affected as the water to rice ratio increased. The modified balances generally increased as grains became shorter, while, |G*| increased and tanδ decreased as the grain became longer. These results were also closely related to the amylose content of each rice variant. Waxy rice (few amylose content) was least firm and highest modified balance, lowest |G*| and highest tanδ, while the results of rice with the highest amylose content showed the opposite results. Principal component analysis revealed that the modified balance, tanδ, firmness and |G*| were located in similar ordinates, indicating that the variables of the two different tests were closely related. Overall, these results demonstrate that some variables in the two different tests provide the same type of information and complementary explanation.